The Primaku application is effective in monitoring early childhood growth and development through parental assistance - Dais, Exsos Grend; Wahyuni, Emmy Putri; Lusty, Junita; Ruriwinita, Ruriwinita; Fitriyati, Fitriyati; Mursiah, Mursiah; Fitriana, Anantusia; Karwati, Eti; Sofyan, Evi; Purwati, Nyimas Heny; Sutini, Titin; Apriliawati, Anita (Riset Informasi Kesehatan, 2025)
Background: Early childhood growth and development disorders are still a concern for parents today, especially stunting. Monitoring early childhood growth and development is still a difficulty for parents today. Lack of access to digital-based information about children's health information makes it easy for parents to underestimate this so that it is too late to take care of it. So, it is necessary to have an application for monitoring the growth and development of early childhood based on digital. Objectives: This study aims to determine the effect of the PrimaKu application on the assessment of early childhood growth and development through parental assistance. Methods: This study is a quantitative study with the type of Pre-Experiment, using the One Group Pretest-Posttest research design by providing parental assistance intervention using the PrimaKu Application in one meeting. The effect of the intervention was measured by comparing pre-test and post-test scores. Bivariate analysis was performed using the Wilcoxon Test. Results: The results of the analysis obtained a p-value: 0.001 (p <0.05) with a median pre-test>post-test value, namely 80.00>50.00 with a difference of 30.00. The minimum pre-test>post-test value, namely 50>30 with a difference of 20. The maximum pre-test>post-test value, namely 100>90 with a difference of 10. Conclusion: There is an effect of the PrimaKu application on the assessment of early childhood growth and development through parental assistance. So, that the use of the PrimaKu application is highly recommended for parents to use in assessing early childhood growth and development.